CHARACTERISTICS OF ADVOCACY IN LITHUANIA. RESULTS OF EXPERT INTERVIEWS - Batysukova, S. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article reflects upon advocacy characteristics in Lithuania, that is consolidated democracy and the country with ‘free’ freedom status. Among advocacy characteristics, the author focused on the following five: massiveness, focus on interests/ rights/ values, purpose, targets and agents, level of advocacy implementation. Descriptive characteristics of advocacy are presented in the article based on the quality interviews conducted with Lithuanian and international experts.